(untitled) (Journal of Educational Sciences, 2023)
Training of competitive specialists who meet the requirements of the society is a requirement of the time. One of the components of the professional success of a modern teacher is continuous education and development of professional competence within the framework of mastering new means of ensuring professional excellence. Every teacher should strive to achieve success in addition to imparting the required level of knowledge to the student.The article reveals the competency-based approach to teaching and its role in teaching language disciplines. The issues of creating social conditions for the formation of professional competencies of the personality of a future specialist are raised. The concepts of “competence” and “competence” are analyzed and the system of competencies and competencies operating in modern education is determined. The differences in the meaning of the concepts “competence” and “competence” are shown. Characteristics of the content and types of competencies in practice in different countries of the world are given, and the experience of Kazakhstan is analyzed. The importance of teaching the native language in the context of intercultural communication and multiculture is confirmed. The content of key competencies required in a modern knowledge society has been clarified. The importance of language disciplines in the formation of these competencies is emphasized. 75 students of Faculty of Philosophy and Political Science of Al-Farabi Kazakh National University took part in the practical part of the study. Keywords: competency, competence, language subjects, social and ethical competence, linguistic competence, intercultural communication.